Judging heterodox economics: A response to Hodgson's Criticisms - Lynne Chester (Economic Thought, 2019)
The renowned institutionalist Geoffrey Hodgson has claimed inter alia that heterodox economics has failed to define its nature and scope, does not take pluralism seriously, and lacks expertise concentration to ensure quality which means it has made limited progress and is held in variable esteem. To address these alleged problems, Hodgson proposes four alternative strategies: the creation of heterodox economics academic departments; for heterodox economists to enter non-economics academic departments; for heterodox economists to "organise" around a successful approach with future potential; or, to encourage the study of economic institutions by other social science disciplines or by using prominent mainstream techniques and approaches. A response to these criticisms and proposed strategies is warranted for several reasons. These criticisms are not trivial and, as an assemblage the import is much greater than a singular criticism. Hodgson is very influential within the economics discipline and he reiterates, in part, past criticisms from the mainstream as well as presenting his criticisms to a wide range of audiences. These criticisms intersect with longstanding debates within heterodox economics about the role of pluralism, the definition and project of heterodox economics, its relationship to the changing form of mainstream, and the merit of synthesis or convergence of different heterodox schools of economic thought. The suitability of mainstream measures to judge heterodox economics, and the relationship of ideology and economic theory, are also raised by these criticisms as well as the feasibility of proposed strategies to support heterodox economics within the academy. It is argued that several fallacious claims lead Hodgson to misconstrue the nature and evolution of heterodox economics, and inherent flaws in each of his proposed alternative strategies will further marginalise - not advance - the project of heterodox economics.
Keywords: B40; B50; B59; 330; heterodox economics; Geoffrey Hodgson; methodology; ontology; pluralism